(untitled) (RuMoRes, 2023)
This article analyzes Tempos de paz (2009), a Brazilian historical drama directed by Daniel Filho and based on a play by Bosco Brasil. Exploring the theme of migration and cultural citizenship, the narrative interconnects different approaches that when articulated s, allow us to apprehend the work’s meanings regarding social memory, the subjection and subjectivation processes, and the interweaving between its aesthetic and political field, even touching on the human substance. Its hybrid narrative format (in dialogue with the theater) culminates, in its ending, by validating the film’s larger enunciative scene, which is an homage to different and important immigrants who contributed to Brazilian culture, research and knowledge aspects.